Health, Quality of life and substances consume and length of homelessness. - Panadero-Herrero, Sonia; Muñoz-López, Manuel (Anales de Psicología / Annals of Psychology, 2013)
The study investigated main characteristics of “new” homeless people vs. “old” or “chronic” homeless people. Specifically this paper presents the differences in relevant variables (quality of life, health, alcohol and drug consume) between homeless people who were homeless less than one year and those who were more than five years in this situation. Aim of that is to investigate the effect of length of homelessness and identify differential variables that permit to recognize specific needs and planning services and resources for each group and moment. Results show important differences between both of groups: higher deterioration among long-term homeless (higher alcohol and drugs consume, disabilities) and more difficulties (more rough sleepers, begging, etc.).